The influence of the boundary conditions on low-velocity impact composite damage - Amaro, A. M. (2014)
The objective of this work was to study the influence of the boundary conditions on low-velocity impact behaviour of carbon-epoxy composite plates. Experimental work and numerical analysis were performed on [04,904]s laminates. The influence of different boundary conditions on the impacted plates was analysed considering rectangular and square plates. The X-radiography was used as a non-destructive technique to evaluate the internal damage caused by impact loading. A three-dimensional numerical analysis was also performed considering progressive damage modelling. The model includes three-dimensional solid elements and interface finite elements including a cohesive mixed-mode damage model, which allows simulating delamination between different oriented layers. It was verified that plate’s boundary conditions have influence on the delaminated area. Good agreement between experimental and numerical analysis for shape, orientation and size of the delamination was obtained.